Electrical and optical properties of N, N`-bis (Inaphthyl)-N,N`-diphenyl-1,1`-biphenyl-4,4`-diamine as hole transport layer in organic light emitting devices - Lim, Mei Yee; Mat Yunus, Wan Mahmood; Talib, Zainal Abidin; Kassim, Anuar; Dee, Chang Fu; Ismail, A. (Science Publications, 2010)
Problem statement: The aim of this research was to study the electrical and optical properties of N, N`-bis(Inaphthyl)-N,N`-diphenyl-1,1`-biphenyl-4,4`-diamine (NPB) organic materials often used as hole transport layer in Organic Light-Emitting Devices (OLED). Approach: The NPB layer was prepared using the thermal evaporation method. From photoluminescence spectra, two peaks at 630 and 480 nm were observed with 55 nm NPB. The electrical conductivity was strongly influenced by the layer thickness. Results: The energy band gap of each NPB layer was successfully presented in the range of 2.4-2.9 eV. Conclusion: This study successfully showed the effect of different thickness of NPB in OLED.